New year, new phase for QOE-IJES - Paolo Bellucci; Silvia Bolgherini (QOE-IJES)
With the current issue, the first of 2020, Quaderni dell’Osservatorio Elettorale – Italian Journal of Electoral Studies enters a new stage of its long life as a journal devoted to publishing high-quality articles in the field of election studies. This forty-third birthday signals many changes: with its new Italian-English name and acronym, QOE-IJEL becomes the official journal of the Italian Society for Electoral Studies (SISE – Società Italiana di Studi Elettorali), appoints new editors and editorial team, and migrates to a new publisher.